(untitled) (Bangladesh Journal of Medical Physics, 2013)
The present work envisages mathematical modeling of induced focal cerebral ischemia in animal model using EEG data with the help of Fast Fourier Transformation method. Amongst several analysis methods, spectral analysis methods are important because it detects the frequencies and characteristics changes of brain waveforms depending on the brain function affected from disorders and physiological state. There are many applications of FFT, and the most important being that it is one of the basic conventional spectral analysis methods. However, it has some limitations, for instance, it adds contributions in the low frequency region which are not present in the original signal, and necessitates the use of windowing for decreasing the error rate. The present analysis was undertaken to ensure actual correlation of the different mathematical paradigms. EEG data were obtained from different regions of rat brain and were processed by FFT modeling in MATLAB platform. The assessment of long lasting functional outcome and to prevalent classical approach to study stroke was necessitated and therefore highly recommended to evaluate the efficacy of therapeutic strategies in relation to EEG in animal model of brain stroke. This mathematical modeling specifically Power Spectrum Density analysis was done to correlate the different prevalent condition of rat brain function. DOI: http://dx.doi.org/10.3329/bjmp.v5i1.14666 Bangladesh Journal of Medical Physics Vol.5 No.1 2012 29-36